Bioactive Molecules from the Invasive Blue Crab Callinectes sapidus Exoskeleton: Evaluation of Reducing, Radical Scavenging, and Antitumor Activities - Francesco Longo; Alessandro Attanzio; Laura Marretta; Claudio Luparello; Serena Indelicato; David Bongiorno; Giampaolo Barone; Luisa Tesoriere; Ilenia Concetta Giardina; Giulia Abruscato; Manuela Perlotti; Lucie Branwen Hornsby; et al. (Marine Drugs)
In recent years, the invasive Atlantic blue crab (Callinectes sapidus) has increased its spread throughout the Mediterranean Sea, threatening native biodiversity and local economies. This study aimed to valorize C. sapidus sampled in Sicily by utilizing its exoskeleton as a source of chitosan, astaxanthin, and bio-phenolic compounds. These biomolecules were evaluated for their reducing, radical scavenging, and antitumor activity. The ferric ion reducing antioxidant power (FRAP) and the free radical scavenging activity against radical 2,2-Diphenyl-1-picrylhydrazyl (DPPH) were significantly higher for chitosan (3.16 ± 0.10 mg AAE/g and 8.1 ± 0.10 µmol TE/g). No significant differences were observed among the tested biomolecules in their activity in scavenging the radical 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS). Both bio-phenolic compounds and astaxanthin exhibited dose-dependent cytotoxicity on CaCo-2 (IC50 = 12.47 and 18 µg/mL) and HepG2 (IC50 = 10.25 and 1.26 µg/mL) cell lines, while only bio-phenols showed no cytotoxic effect on differentiated CaCo-2 cells up to 20 µg/mL. These findings highlight the value of blue crab by-products in supporting a circular economy, offering a sustainable approach to managing this invasive species while providing bioactive compounds with promising medical and nutraceutical applications.